A Balanced Scorecard for Maximizing Data Performance - Pierce, Elizabeth (Frontiers in Big Data, 2022)
A good performance monitoring system is crucial to knowing whether an organization's efforts are making their data capabilities better, the same, or worse. However, comprehensive performance measurements are costly. Organizations need to expend time, resources, and personnel to design the metrics, to gather evidence for the metrics, to assess the metrics' value, and to determine if any actions should be taken as a result of those metrics. Consequently organizations need to be strategic in selecting their portfolio of performance indicators for evaluating how well their data initiatives are producing value to the organization. This paper proposes a balanced scorecard approach to aid organizations in designing a set of meaningful and coordinated metrics for maximizing the potential of their data assets. This paper also discusses implementation challenges and the need for further research in this area.